2013
DOI: 10.2337/db12-0507
|View full text |Cite
|
Sign up to set email alerts
|

The Suprachiasmatic Nucleus Controls Circadian Energy Metabolism and Hepatic Insulin Sensitivity

Abstract: Disturbances in the circadian system are associated with the development of type 2 diabetes mellitus. Here, we studied the direct contribution of the suprachiasmatic nucleus (SCN), the central pacemaker in the circadian system, in the development of insulin resistance. Exclusive bilateral SCN lesions in male C57Bl/6J mice, as verified by immunochemistry, showed a small but significant increase in body weight (+17%), which was accounted for by an increase in fat mass. In contrast, mice with collateral damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 51 publications
6
110
0
3
Order By: Relevance
“…Both rodent and human studies confirm that daily rhythms of blood glucose and insulin secretion are regulated by the timing system [53][54][55], whilst lesions of the SCN or environmental circadian disruption can lead to insulin resistance and obesity [56,57]. The molecular clock is essential for glucose metabolism, as evidenced by the impairment of glucose tolerance and insulin sensitivity upon disruption of core clock gene expression [51,[58][59][60][61][62][63].…”
Section: The Timing System and Glucose Homeostasismentioning
confidence: 92%
See 1 more Smart Citation
“…Both rodent and human studies confirm that daily rhythms of blood glucose and insulin secretion are regulated by the timing system [53][54][55], whilst lesions of the SCN or environmental circadian disruption can lead to insulin resistance and obesity [56,57]. The molecular clock is essential for glucose metabolism, as evidenced by the impairment of glucose tolerance and insulin sensitivity upon disruption of core clock gene expression [51,[58][59][60][61][62][63].…”
Section: The Timing System and Glucose Homeostasismentioning
confidence: 92%
“…Though SCN-driven neuroendocrine and autonomic outflow influence glucose homeostasis [64], peripheral clocks in the liver and pancreas also play a role in glucose management [10,[65][66][67][68][69]. We will avoid discussion of SCN-driven cues here, as their contribution has been reviewed elsewhere [10,56,64,70,71]. Instead, we will focus on clock function within the liver and pancreas as it relates to direct tissue level control of glucose homeostasis.…”
Section: The Timing System and Glucose Homeostasismentioning
confidence: 99%
“…The SCN-controlled biological clock rhythm is crucial for maintaining hepatic insulin sensitivity (6). In the current study, we investigated the underlying mechanisms and found that 1) hypothalamic orexin bidirectionally regulates hepatic gluconeogenesis via control of autonomic balance, leading to generation of the daily blood glucose oscillation.…”
Section: Discussionmentioning
confidence: 88%
“…The daily rhythm of HGP is regulated by the autonomic nervous system under SCN control, leading to generation of a daily rhythm in basal blood glucose levels independently of the feeding rhythm (5). The central clock is also crucial for preventing metabolic abnormalities in the liver, since lesions of the SCN caused severe hepatic insulin resistance in mice (6); however, the underlying mechanisms remain uncertain. It is of note that nutrient excess causes endoplasmic reticulum (ER) stress in hepatocytes, a main cause of hepatic insulin resistance, and the cells need "resting time" to recover from the ER stress (7,8).…”
mentioning
confidence: 99%
“…Peripheral circadian oscillators have been demonstrated in both white and brown adipose tissues that play a prominent role in energy conservation and adaptive metabolic responses [68][69][70]. Additionally, normal satiety hormone levels, such as leptin [71], ghrelin [72], insulin [73], and glucagon [74], tend to exhibit circadian oscillation. Finally, functional connections between core clock genes and metabolic processes are increasingly being characterized using mutant mice.…”
Section: Circadian Clock and Metabolismmentioning
confidence: 99%